Supply-demand spatial patterns of park cultural services in megalopolis area of Shenzhen, China - Zhenhuan Liu (Elsevier, 2021)
Rapid urbanization has created daunting challenges with respect to the demand for cultural ecosystem services (CES). Recreation is a special CES provided by the biophysical properties of parks in the city. However, assessment of the CES of parks remains challenges partly due to the lack of appropriated framework at community level, and partly because of paucity of information on park demand. This study uses spatially explicit approaches including recreation accessibility and potential indicators and multi-sources data such as crowd-sourced information form Point of Interests (POIs) to map the supply and demand for CES of parks. Then, the spatial statistics were used to identify unbalanced communities to reveal the pattern to support landscape planning at the city scale. The results show that 33.76% of Shenzhen’s community, concentrated in the central urban area, was characterized by a large supply of CES with a strong spatial aggregation. A total of 39.4% of the communities had high demand for CES, and were scattered in the central urban areas and suburbs. This mismatch in distribution shows that 29.8% of the communities had inadequate supply relative to demand. Moreover, 5% of the communities were prioritized to plan new parks while only 2.6% had the potential to share their services. The new park planning priority was determined according to the significance of low supply-high demand communities and its surroundings, which helped for local development planning. This study provides a comprehensive spatial way to make park planning and management in rapidly urbanizing areas.